The National-International Power of the States. A Trans-Structural Proposal - Rocha Valencia, Alberto; Morales Ruvalcaba, Daniel (Geopolítica(s). Revista de estudios sobre espacio y poder, 2018)
The question of national power remains in a situation of controversy and debate in International Relations. From the theoretical level, the problem lies in its definition, in the constitutive dimensions and the variables considered; from a technical point of view, the question is its measurement. For us, the national-international power of a State is the product of the multidimensional, dynamic and recursive combination of its capacities and is expressed in a specific historical moment of the development of the international system. Very briefly, we can say that these capacities are grouped into three major categories: 1) the material capacities, 2) the semi-material capacities, and 3) the immaterial capacities. These capacities are the constituent elements of three types of power: material power, semi-material power and immaterial power. Based on the three sets of capacities, the World Power Index is produced, which will allow measuring the national-international power of the States year by year. Starting from the theoretical postulates proposed by the main paradigms of International Relations, this document is focused on capturing a proposal for the study of national power in our days.
Keywords: national-international power; national capacities; Theories of International Relations; international politi-cal system; World Power Index